A RARE CASE OF ISCHEMIC STROKE IN A YOUNG WOMAN WITH AUTOIMMUNE DISEASE: DIAGNOSIS AND THERAPY CHALLENGES - Bulain, Stanley; Atalia, Arila; Lestari, Hotma; Pamarta, Trisna Belani; Rakhmatiar, Rodhiyan (Journal of Pain, Headache and Vertigo, 2025)
Introduction: Stroke is a leading cause of death and disability worldwide and is considered a disease of the elderly. However, recent trends indicate an increase in stroke cases in young adults due to autoimmune causes. Stroke in young adults directly impacts health, productivity, society, the economy, and the health system. Case: A 30-year-old woman presented with sudden, intermittent weakness of one half of her body for 2 days. Physical examination revealed mild paralysis of the right 7th and 9th nerves, hemiparesis, hemihypesthesia, hemiparesthesia, increased physiological reflexes, and positive Hoffman and Tromner reflexes in the right extremity. A CT scan was normal, and the ANA test was positive. The patient was hospitalized for 7 days and given citicoline 500 mg once, azathioprine 50 mg twice, hydroxychloroquine 1200 mg once, acetylsalicylic acid 200 mg once, and pulse methylprednisolone 125 mg four times. She gradually improved. The patient was referred to the RSSA for MRI and MRA, which revealed a chronic infarction extending from the corona radiata to the left lentiform nucleus and no visible ACA segment A1 structure. The patient experienced a generalized tonic-clonic seizure lasting 2 minutes during the DSA. Diazepam 7.5 mg, Metamizole 1 g, and Nicardipine 3 mg/hour were administered, and the patient subsequently regained consciousness. The DSA results showed total occlusion of the ACA segment A1. The patient was diagnosed with CVA infarction with total occlusion of the ACA segment A1, with suspected autoimmune disorder. The patient was discharged three days later and planned for observation. Conclusion: Ischemic stroke in young adults with autoimmune disorders is a serious condition that requires special attention. Antiphospholipid antibody-related hypercoagulability and vascular complications such as vasculitis are the main mechanisms of stroke in this population. Further evaluation for underlying autoimmune disease is necessary for further treatment decisions.